A Sustainable Practices of Utilizing Ceramic Tile Waste to Replace Coarse Aggregate in Normal Concrete - Lim, Xi Yi; Zainun, Noor Yasmin; Mohd Hilton Ahmad,; Mansor, Hazrina (International Journal of Integrated Engineering, 2025)
Due to poor construction waste manegement and disposal problem, construction waste is an emerging issue in the Malaysian Construction Industry (MCI). Massive construction projects affect the environment and produce huge amount of construction waste, including ceramic tile waste. The research aim is to figure out the mechanical characteristics of normal concrete under compressive strength and four-point bending tests with different percentages of ceramic tile waste replacement. Ceramic tile waste is recycled to replace coarse aggregate in developing a designed strength of 30 N/mm2 at 28 days. 10% of the cement is substituted with fly ash. Maximum particle for fine and coarse aggregates are 5 mm and 10 mm in sizes. A uniform ratio of 0.545 water-to-cement (w/c) and a concrete mix ratio of 1:2.61:2.71 (Cement: Fine aggregate: Coarse aggregate) are applied in the Department of Environment (DOE) technique. Thirty-six-cylinder specimens (150 mm X 300 mm) and eighteen prism specimens (400 mm x 100 mm x 100 mm) are casted, cured and tested to examine their properties. 20% crushed gravel is replaced with ceramic tile waste to obtain higher compressive and flexural strengths, measured 39.21 N/mm2 and 3.51 N/mm2 respectively. By turning waste into wealth, this research can reduce the dependency on natural raw materials, recycling recyclable resources, reduce the disposal of ceramic tile waste and minimize negative impacts on the environment.